SISTEM INFORMASI MANAJEMEN PERIZINAN REKLAME PADA SUKU DINAS PENDAPATAN DAERAH WILAYAH JAKARTA BARAT II - ADE KURNIAWAN; ISTIQOMAH ISTIQOMAH (Jupiter: Journal of Computer & Information Technology, 2020)
The implementation of regional government and regional development in its implementation very much dependent on the regional genuine revenue (PAD), while the largest PAD of DKI Jakarta province comes from local taxes. Thereby the implementation of PAD reception needs to be optimized. Looking for sources of the new funds in the reform it is very problematic because new charges should align with an increase in services and not burden the public and the business world. The safest way is to optimize existing tax collection, one of them potentially is advertisement licensing which includes advertisement tax. In the licensing process is required an information system so that the licensing process may go in good and smooth. After conducting research on an existing system, there are still several weaknesses among them are operational service administration and calculations were done manually, the process of data storage/files and for finding data required information not arrayed or not well integrated, and reporting data information is still limited so that takes a long time to prepare. In the journal was discussed about the design of a new information system that in order to minimize that several weaknesses. The use of a computer in the new information system is expected to shorten the time needed for data processing and preparing the report.